RETRACTED: Vibratory interactions in sports equipment on laboratory test-beds - Minaev Andrey; Minaev Anton (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001